Social Cohesion and Its Relation to Health Awareness among Female Kindergarten Students (Journal Of Educational and Psychological Researches, 2024)
The current research aims to identify social cohesion and its relation to health awareness among female students in the kindergarten department. The researcher developed two scales for each of social cohesion, consisting of 25 items, and health awareness, consisting of 24 items. The study sample consisted of 200 female students from the kindergarten department. The results concluded that female kindergarteners have social cohesion and health awareness. There is a correlation and significant contribution between social cohesion and health awareness among students